Ekologi Ikan Wild Betta Endemik Betta Schalleri asal Perairan Bangka - Lindiatika, Lindiatika; Khanati, Olivia; Lista, Dona; Syarif, Ahmad Fahrul (Seminar Nasional Lahan Suboptimal, 2023)
Lindiatika, L., Khanati, O., Lista, D., & Syarif, A. F. (2023). Ecology of endemic Wild Betta Fish Betta Schalleri from Bangka Waters. In: Herlinda S et al., (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 507-512). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Wild Betta (Betta Schalleri) is a nature betta fish which is generally knows as tepalak/tempalak which is spread in the waters of Bangka Belitung Island, and its existence is now increasingly difficult to find in its natural habitat. This research aimed to examine the conditions of the aquatic environment and ecology to determine the characteristics of the natural habitat which can be the main factor in the existence of Wild Betta fish (B. Schelleri). Since its existence is difficult to find in its natural habitat, it is necessary to conduct an assessment of the condition of the aquatic environment and its ecology in order to carry out the conservation phase. Research carried out in the rivers of Bangka district in July – October 2023 discusses the ecology of Wild Betta (B. Schalleri), the results showed that in general Betta Schalleri inhabits peat swamp waters and small waterways with low pH which are grown with aquatic plants are Pandanus sp, Cryptocorine sp, Hydrilla sp, Vellisnaria sp, and Utrikularia sp, and have aslightly brownish water color with a wet soil substrate texture containing peat. In this study, water quality measurements were carried out and the values obtained were Temperatu Water conditions and ecology are needed to determine the characteristics of the natural habitat which can be the main factor in the existence of Wild Betta fish (B. Schalleri). re (31°C), pH (4 -5), and also found several biota associated with Betta Schalleri.